Pregnancy outcomes, risk factors, and cell count trends in pregnant women with essential thrombocythemia. (November 2020) - How, Joan; Leiva, Orly; Bogue, Thomas; Fell, Geoffrey G.; Bustoros, Mark W.; Connell, Nathan T.; Connors, Jean M.; Ghobrial, Irene M.; Kuter, David J.; Mullally, Ann; Neuberg, Donna; Zwicker, Jeffrey I.; et al.
Highlights: We evaluated risk factors in 121 essential thrombocythemia pregnancies. Half of all women experienced a complication, the most common being spontaneous abortion. Aspirin use and prior pregnancy loss are associated with decreased and increased risk of complications, respectively. Platelet counts decrease more in essential thrombocythemia pregnancies compared to normal populations. Greater gestational platelet count declines are associated with improved outcomes. Abstract: Pregnancy in essential thrombocythemia (ET) is associated with increased risk of obstetric complications. We retrospectively evaluated risk factors in 121 pregnancies in 52 ET women seen at 3 affiliate hospitals. Univariable and multivariable analyses were performed at the α = 0.10 level. Cell counts were characterized throughout pregnancy and correlated with outcomes using logistic modeling. The overall live birth rate was 69 %. 48.7 % of all women experienced a pregnancy complication, the most common being spontaneous abortion, which occurred in 26 % of all pregnancies. Maternal thrombosis and hemorrhage rates were 2.5 % and 5.8 %. On multivariable analysis, aspirin use (OR 0.29, p = 0.014, 90 % CI 0.118–0.658) and history of prior pregnancy loss (OR 3.86, p = 0.011, CI 1.49–9.15) were associated with decreased and increased pregnancy complications, respectively. A Markov model was used to analyze the probability of a future pregnancy complication based on initial pregnancy outcome. An ET woman who suffers a pregnancy complication has a 0.594 probability of a subsequent pregnancy complication, compared to a 0.367 probability if she didn't suffer a complication. However, despite this elevated risk, overall prognosis is good, with a >50 % probability of a successful pregnancy by the third attempt. Platelet counts decreased by 43 % in ET during pregnancy, with nadir at delivery and prompt recovery in the postpartum period. Women with larger declines in gestational platelet counts were less likely to suffer complications (p = 0.083). Our study provides important guidance to physicians treating ET women during pregnancy, including counseling information regarding risk assessment and expected trajectory of platelet levels.